Interpersonal Communication Patterns of Foster Parents and Dropping out Children in School at Social Rehabilitation Center for Delinquents UPT PSMP TENGKU YUK PEKANBARU - Aqilla Putri Herta; Nofha Rina (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The pattern of interpersonal communication is the most effective communication to use a direct approach personally between the communicator and the communicant, so that it is more intense. For Drop Out children, who come from different backgrounds, ordinary communication approaches, such as socialization or seminars, cannot be used, they will not focus on listening to the messages conveyed by the communicator, and tend not to pay attention to the messages. The aim of this study was to identify the Communication Patterns of Foster Parents and School Dropouts at the Social Rehabilitation Center for Naughty Children UPT. Tengku Yuk PSMP Pekanbaru. The author applies a qualitative descriptive research method in this study. This study also uses an emotional approach, which in communication becomes the ability to position oneself in the interlocutor. The object of this research is the Social Rehabilitation Center for Naughty Children, UPT. PSMP Tengku Yuk Pekanbaru, which is a rehabilitation center for troubled naughty children. In this study, respondents as a sample were determined through the purposive sampling method. Based on the results of research in the field, the authors found the fact that the pattern of interpersonal communication applied by foster parents to foster children at UPT PSMP Tengku Yuk has not been implemented properly. Where the indicators of "communicator" and "media" in interpersonal communication patterns have not been maximized.